COGNITIVE DEVELOPMENT OF ENGLISH HYDRONYMS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article discusses the cognitive aspects of English hydronyms and provides a scientific rationale for the language and cultural influences associated with naming, an interdisciplinary integration that brings together historical and cognitive linguistics as well as cultural analyses. The study highlights the etymological roots, semantic evolution and cultural significance of English hydronyms. By tracing the historical layers of linguistic influence and analysing the cognitive motives for hydronym formation, the relationship of English hydronyms to historical events, cultural identity and environmental descriptions is revealed. Valuable insights into the cognitive and cultural heritage of English-speaking communities are presented.